Assessment of the antioxidant ability of Thymus albicans, T mastichina, T camphoratus and T carnosus essential oils by TBARS and micellar model systems. - Miguel, Maria Graça (2015)
The essential oils isolated by hydrodistillation from different populations of Thymus albicans, T mastichina, T carnosus and T. camphoratus, collected during the vegetative phase, were analysed by GC and GC-MS. The same oils were used in the antioxidant activity evaluation using.the TBARS assay and the micellar model systems. T albicans oils and two of the oils from T. mastichina populations were 1,8-cineole-rich. The third T mastichina oil was linalool-rich. trans-Sabinene hydrate, bomeol and linalool in similar amounts, and 1,8-cineole were the main components of the oils from each of the three populations of T camphoratus. T carnosus oils were mainly composed of borneol. All essential oils revealed some degree of antioxidant activity either in the presence or absence of ABAP in the TBARS method. The micellar model system showed higher antioxidant indices than those obtained by the TBARS method.